Determining the key factors of corporate leverage in Indian manufacturing firms using dynamic modelling - Ishfaq Gulzar; S.M. Imamul Haque (Cogent Business & Management, 2022)
Using a data set of Indian Manufacturing companies (NSE 500), this paper examines the relationship between corporate governance characteristics and firm-specific factors in predicting leverage decisions of a firm. The paper specifies partial adjustment model and utilises System Generalised Method of Moments (GMM) to find out the factors affecting speed of adjustment. The results of this study show that non-debt tax shield positively affects SOA, whereas growth, tangibility and firm size negatively influence SOA. In the case of corporate governance variables, board size, board independence, ownership concentration and corporate governance index reveal a positive influence on SOA. The paper also confirms that it takes around 2.65~years to offset half of the target leverage from current leverage.
Keywords: 650; Corporate governance; leverage; Generalised Method of Moments (GMM); speed of adjustment